Dampak Praktis Teologi Aswaja di Nusantara terhadap Modernisasi Beragama dalam Konsep Iman dan Akhlak - Fadhlan Kamali Batubara; Muhammad Fadhil; Khaila Shafa Suhanda; Al Kausar Annur; Rizky Aulia Romarito Sormin; Muhammad Fikri Syahdi Siregar (UIN Sumatera Utara, 2026)
This study examines Ahlussunnah wal Jama’ah (Aswaja) as a moderate Islamic paradigm encompassing theology, jurisprudence, and Sufism, as well as its relevance in addressing contemporary challenges. The objective of this research is to analyze the concepts of faith, ethics, and religious moderation within the Aswaja framework, along with their implementation in social life and digital preaching. The research employs a qualitative approach using library research and content analysis of social media platforms such as TikTok and YouTube. The findings reveal that the concept of faith in Aswaja consists of three essential components: affirmation in the heart, declaration through speech, and manifestation in actions. In terms of ethics, Aswaja emphasizes the development of inner character that naturally drives good behavior. The core principles of religious moderation in Aswaja include tawassuth (moderation), tasamuh (tolerance), tawazun (balance), and ta’adul (justice), supported by additional values such as musawah (equality), syura (consultation), ishlah (reform), and aulawiyah (prioritization). In the digital era, these values are represented through inclusive, contextual, and non-extremist preaching, making them effective in reaching younger audiences and responding to diverse societal dynamics. This study concludes that the digitalization of Aswaja preaching serves as a crucial strategy in strengthening the narrative of moderate Islam that is tolerant, adaptive, and relevant in the face of globalization and technological advancement.